Playtime: in the night garden (Penguin group London, 2008)
"Playtime" is a vibrant children's book that celebrates the joy of play and the different activities children can enjoy. It typically features a variety of playful scenarios, showcasing friends engaging in games, sports, and imaginative play. The book emphasizes themes of friendship, creativity, and the importance of play in childhood development. With colorful illustrations and engaging text, it encourages young readers to embrace their playful spirits and explore the fun of spending time with others.